2010
DOI: 10.1016/j.eurpsy.2010.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Orbitofrontal morphology in people at high risk of developing schizophrenia

Abstract: Our results suggest that OFC Type III is associated with psychotic features before the development of schizophrenia. Characterisation of OFC morphology may have a role in the identification of those at greatest risk of developing schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
63
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(77 citation statements)
references
References 34 publications
11
63
3
Order By: Relevance
“…There already are many studies that classify the orbitofrontal sulcus and gyrus based on magnetic resonance images and our results were very similar to theirs results 6,7,9,10,11 . For instance, Chiavaras and Petrides (2000) The fact that our results were similar to previews radiological studies 6,7,9,10,11 aggregate evidence in the anatomical characterization of the orbitofrontal cortex, as there are two different methods to investigate the same issue with similar results.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…There already are many studies that classify the orbitofrontal sulcus and gyrus based on magnetic resonance images and our results were very similar to theirs results 6,7,9,10,11 . For instance, Chiavaras and Petrides (2000) The fact that our results were similar to previews radiological studies 6,7,9,10,11 aggregate evidence in the anatomical characterization of the orbitofrontal cortex, as there are two different methods to investigate the same issue with similar results.…”
Section: Discussionsupporting
confidence: 81%
“…We also divided the orbitofrontal cortex general configuration according to Chiavaras' classification modified by Charikova et al 6,7 . In this classification, the type I pattern is characterized by a continuous lateral orbital sulcus and a clearly distinct anterior medial and posterior medial orbital sulcus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, altered sulcogyral patterns in the orbitofrontal cortex (OFC), a key brain region involved in odor hedonic processing and sensory integration, were found to differentiate schizophrenia patients and individuals who convert to schizophrenia from non-converters and controls (Chakirova, Welch et al, 2010; Nakamura, Nestor et al, 2007). Therefore, odor valence measures, reflective of both hedonic disturbance and orbitofrontal impairment, could have predictive utility in identifying those at risk for the development of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of 40 healthy adults (Kapogiannis et al, 2009a), investigators found that key components of religiosity (having intimate relationship with God and religious behaviors, as well as fear of God) were associated with structural differences including a decrease in the left orbitofrontal cortex (OFC). This is particularly interesting as the OFC is integral to higher order cognitive function including emotional processing, motivation, decision-making, hedonic experience, and sensory-visceral multimodal experience (Öngür and Price, 2000; Kringelbach, 2005; Chakirova et al, 2010). Additionally, studies across the psychosis spectrum, including those assessing individuals at high risk, individuals with first-episode psychosis, and those with chronic schizophrenia have found decreased volumes in the OFC (Borgwardt et al, 2008; Chakirova et al, 2010; Jung et al, 2012).…”
Section: Introductionmentioning
confidence: 99%